Intelligent IoT-Based Cross-Border e-Commerce Supply Chain Performance Optimization. (22nd June 2021) - Xia, Lei; Liu, Sitong
Abstract : Internet of Things (IoT) technology can benefit automated production, agriculture, intelligent autonomous driving, and many other industries by using billions of smart devices. As a good example, intelligent IoT and 5G are the main source of information acquisition and play an important role in the multiobjective optimization process of the supply chain. This paper develops an optimal management and coordination method to improve the performance of cross-border e-commerce supply chain by using IoT tracking technique and multiobjective decision-making. The numerical results justify that our proposed scheme has high internal consistency, with the Cronbach's alpha factor of each dimension of the optimized decision model all greater than 80%.